Taxonomic review of the lac insect genus Paratachardina Balachowsky (Hemiptera: Coccoidea: Kerriidae), with a revised key to genera of Kerriidae and description of two new species - Kondo, Takumasa; Gullan, Penny J. (Zootaxa, 2007)
The genus Paratachardina Balachowsky (Hemiptera: Coccoidea: Kerriidae) is revised to include nine species: P. decorella (Maskell), P. minuta (Morrison), P. mithila Varshney, P. morobensis Williams & Watson, P. silvestri (Mahdihassan), P. ternata (Chamberlin), P. theae (Green), and two new species. Tachardina lobata Chamberlin (now P. lobata) is synonymized with Tachardia silvestri Mahdihassan (now P. silvestri), based on examination of type specimens. Paratachardina capsella Wang is transferred to Albotachardina Zhang as Albotachardina capsella (Wang) comb. nov. We provide a revised taxonomic key to the genera of the family Kerriidae and to all known species of the genus Paratachardina. All Paratachardina species are redescribed and illustrated with the exception of P. mithila. One of the new species described here is the polyphagous and pestiferous lobate lac scale, which damages trees and woody shrubs in Florida, U.S.A., the Bahamas and the territory of Christmas Island, Australia, and has been identified mistakenly as Paratachardina lobata (Chamberlin), an insect native to India and Sri Lanka. Here we recognize the lobate lac scale as a new species, name itParatachardina pseudolobata sp. nov. and describe it based on all stages of the female (adult, second instar and first instar). In addition, a second new species, P. mahdihassani sp. nov., is described based on adult females from India.